2018
DOI: 10.3389/fmed.2018.00287
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Music and Music Therapy in Ameliorating Depression Symptoms and Improving Well-Being in Nursing Home Residents With Dementia

Abstract: Background: Studies have shown music therapy can improve depression symptoms in dementia and the use of music activities show promise to have positive impacts on wellbeing. However, few studies show the influence of a music intervention led by certified nursing assistants (CNAs) trained by music therapists to address depression symptoms and wellbeing in individuals with dementia.Methods: Credentialed music therapists (1) administered 2-weeks of music therapy, (2) a 3-days training to CNAs, (3) followed by 2-we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 24 publications
4
28
0
1
Order By: Relevance
“…Our ndings presented a nexus of 'music, mind, and well-being' regardless of the age and gender of the residents with advanced dementia. Similar to the current literature, this study's ndings reported that the residents had an opportunity for memory connection, leading to a self-expression, because of the music intervention (Ray & Götell, 2018;Cohen et al, 2020). The 's memory connectedness was related to the tempo, dynamic, and style of the music; and their expressions [i.e.…”
Section: Discussionsupporting
confidence: 81%
“…Our ndings presented a nexus of 'music, mind, and well-being' regardless of the age and gender of the residents with advanced dementia. Similar to the current literature, this study's ndings reported that the residents had an opportunity for memory connection, leading to a self-expression, because of the music intervention (Ray & Götell, 2018;Cohen et al, 2020). The 's memory connectedness was related to the tempo, dynamic, and style of the music; and their expressions [i.e.…”
Section: Discussionsupporting
confidence: 81%
“…In these patients, neuropsychiatric symptoms have been associated with dementia severity, with most symptoms occurring in patients presenting severe cognitive decline 45 . Individuals with dementia are at risk of developing depression due to memory loss, which can lead to loss of independence and social isolation 46 . Dementia alone is a predictor of institutionalization, especially due to the caregiver burden 8,47 .…”
Section: Discussionmentioning
confidence: 99%
“…Ray & Götell 35 measured depressive symptoms using the Cornell Scale for Depression in Dementia (CSDD), 40 and Weise et al 36 measured agitation using the Cohen-Mansfield Agitation Inventory (CMAI). 41 Two studies 34,37 measured psychological wellbeing. Hsu et al 34 measured behavioral well-being using the Dementia Care Mapping, 42 Murphy et al 37 measured mood using a researcher developed scale, and Weise et al 36 measured emotional well-being using the visual analogue scale.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…41 Two studies 34,37 measured psychological wellbeing. Hsu et al 34 measured behavioral well-being using the Dementia Care Mapping, 42 Murphy et al 37 measured mood using a researcher developed scale, and Weise et al 36 measured emotional well-being using the visual analogue scale. For other clinical outcomes, Hsu et al 34 measured the number of antipsychotics and Weise et al 36 measured sleep quality and social participation using the visual analogue scale.…”
Section: Clinical Outcomesmentioning
confidence: 99%